2022
DOI: 10.1097/mpa.0000000000002135
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of Serial Pancreatic Juice Aspiration Cytologic Examination With Brush Cytology for Pancreatic Ductal Stenosis

Abstract: Objectives: Serial pancreatic-juice aspiration cytologic examination (SPACE) is useful for diagnosis of pancreatic ductal stenosis. This study investigates the utility of adding brush cytology to SPACE during the same procedure.Methods: We retrospectively analyzed consecutive patients who underwent SPACE with brush cytology for pancreatic ductal stenosis between February 2014 and July 2020 in our hospital.Results: Thirty-four patients were included. Eleven had lesions in the pancreatic head lesions, and 23 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Yamaguchi et al [ 31 ] reported that brush cytology combined with PJC after brushing significantly increased the diagnostic sensitivity of PDAC. In contrast, Mie et al [ 32 ] retrospectively examined 34 patients who underwent SPACE with brush cytology for pancreatic duct stenosis and reported that the efficacy of adding brush cytology to SPACE was limited. Further prospective studies are required to clarify the effect of brush cytology on the diagnostic yield of PDAC after repeated PJC using an ENPD catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Yamaguchi et al [ 31 ] reported that brush cytology combined with PJC after brushing significantly increased the diagnostic sensitivity of PDAC. In contrast, Mie et al [ 32 ] retrospectively examined 34 patients who underwent SPACE with brush cytology for pancreatic duct stenosis and reported that the efficacy of adding brush cytology to SPACE was limited. Further prospective studies are required to clarify the effect of brush cytology on the diagnostic yield of PDAC after repeated PJC using an ENPD catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that influenced the positive diagnosis were examined, but no significant differences in gender, age, location, or tumor diameter were observed. Mie et al aimed to improve diagnostic performance by combining SPACE with brush cytology, but its effectiveness was limited [26]. Although SPACE and S-PJC have improved diagnostic performance compared to single PJC, no studies have compared the diagnostic performance between the two techniques.…”
Section: Discussionmentioning
confidence: 99%